O ensino de línguas baseado em tarefas e o foco na forma : contributos para uma didáctica do PL2 em Cabo Verde - Pinto, Jorge (Linguarum Arena, 2018)
The main purpose of this article is to present a reflection on the Task Based Language Teaching (TBLT) and the focus on form approach due to the importance they currently have in the learning of an L2 and because they are thought to allow a more efficient and effective learning of Portuguese in Cape Verde. The TBLT aims to develop the students’ interlanguage through the execution of a task in which the students need the language to solve it. By resorting to the focus on form approach we want to call students’ attention to the linguistic forms that come up spontaneously in activities whose main focus is the meaning, which is the case of TBLT. Based on these theoretical principles, we present the partial results of a study that counted with the participation of three Cape Verdean teachers who have adopted the TBLT for a month and have included a focus on form approach for the teaching of grammar as an alternative to the more traditional teaching that predominates in the language lessons.